(3cja Jchf eOQSkG eJejRkG?s - (3GdThjQj, GdjGSs ((3HjQhJs (3OGQ eMLI GdHjVGAs, 2012)
(3GROGO GdGgJeGe HEOGQI GdLhOI GdTGedI aj GdeDSSGJ GdEfJGLjI hGdNOeGJjI NdGd GdYbOjf GdeGVjjf Ydi GdeSJhjjf GdMchej hGdNGU, hCNPJ eeGQSJgG JROGO HTcd JdbGFj habkG debGjjS YGdejI MOOJ dgPG GdZQV(B. (3hdYHJ GdYOjO ef GdYhGed OhQgG GdaGYd aj JRGjO GdGgJeGe HEOGQI GdLhOI GdTGedI, hef CHQR gPg GdYhGed GdJZjQGJ GdGbJUGOjI GdeUGMHI ddGfaLGQ GdYdej hGdJcfhdhLj, hfJjLI ddJhSY aj GdJYdje hRjGOI GdEbHGd Ydjg aj LejY GdeQGMd eeG fJL Yfg RjGOI aj GdcKGaI GdWdGHjI UGMHgG ChLg bUhQ JeKdJ aj YOe GdJfGSH Hjf CYVGA GdgjFI GdJOQjSjI hGdWdGH(B. (3hjMhj gPG GdcJGH CQHYI aUhd JgOa Edi GdJYQja HEOGQI GdLhOI GdTGedI ef MjK eaghegG hCSGdjHgG heRGjGgG hCgejJgG, hEYWGA UhQI hGVMI Yf JWHjbGJ EOGQI GdLhOI GdTGedI aj GdeDSSGJ GdEfJGLjI hGdNOeGJjI hGdJQHhjI heG JhGLgg ef UYhHGJ aj YedjI GdJWHjb, heQGLYI ddOQGSGJ GdSGHbI aj gPg GdeLGdGJ, hfeGPL hebJQMGJ eNJdaI aj GdYOjO ef GdeDSSGJ GdYGdejI hGdYQHjI Ydi GdeLGdGJ GdEfJGLjI hGdNOeGJjI hGdJQHhjI(B.s
(3GdfhY (B: (3cJGHs
Keywords: Performance professionnel; Professional performance; (3GdGOGA Gdegfjs